Urgensi Metodologi Studi Islam Interdisipliner Untuk Moderasi Islam - Theguh Saumantri; Hajam Hajam (Indonesia, 2023)
In the era of globalization and technological advancements, Islam as a world religion faces complex challenges in maintaining teachings that align with the progress of time. To overcome these challenges, a holistic and inclusive approach to understanding and practicing Islam is needed. Interdisciplinary Islamic studies have become an increasingly important topic in the current global context. This is due to the complexity of religious, social, and political issues faced by Muslim communities worldwide. The aim of this research is to uncover the urgency of using interdisciplinary methodologies to promote moderation in the interpretation of religious understanding. Religious moderation refers to a balanced approach between steadfastness in religious principles and flexibility in social contexts. This concept encourages Muslims to understand and practice their religion in an inclusive, tolerant, and adaptable manner to changing times. This research is a qualitative descriptive study conducted using the method of literature review or literary study. The data collection method employed in this research involves reviewing relevant literature from various sources related to the research topic. The selected data is then analyzed using content analysis method. The study concludes that Islamic teachings contain multidimensional aspects, necessitating an interdisciplinary perspective to avoid narrow and exclusive understandings, thus creating a moderate approach to religious practice. This allows us to understand the complexity of Islam and its context in a more holistic and comprehensive manner.